2021
DOI: 10.3389/fgene.2021.654792
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants for Bacterial Osteomyelitis: A Focused Systematic Review of Published Literature

Abstract: Background: Osteomyelitis is an inflammatory process characterized by progressive bone destruction. Moreover, chronic bacterial osteomyelitis is regarded as a difficult-to-treat clinical entity due to its long-standing course and frequent infection recurrence. However, the role of genetic factors in the occurrence and development of bacterial osteomyelitis is poorly understood.Methods: We performed a systematic review to assess the frequency of individual alleles and genotypes of single-nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
5
0
2
Order By: Relevance
“…Genetic polymorphisms in the immune response to infection have been shown to be associated with sepsis and bacterial osteomyelitis; this needs further research. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in the immune response to infection have been shown to be associated with sepsis and bacterial osteomyelitis; this needs further research. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts increase MMP1 expression under the regulation of IL-1 alpha, that the frequency of MMP1 (-1607 2G/2G) genotype in OM patients exhibits, resulting in increased levels of MMP1 2G allele in OM patients, and further promoting local healing of osteomyelitis. [ 31 ] In addition, it has also been discovered that MMP1 can contribute to a reduced risk of osteomyelitis. [ 32 ] In wound healing of DFU, a variety of cells, including fibroblasts, basal cells, and vascular endothelial cells, express MMP1.…”
Section: Discussionmentioning
confidence: 99%
“…Despite appropriate treatments, up to 30% of OM cases become chronic, resulting in serious morbidity and disability and remarkable economic burden [ 66 ]; a genetic predisposing substrate may partly explain these results. Recently, Xie et al analyzed several single-nucleotide polymorphisms (SNPs) of DNA sequences linked to the susceptibility of OM and they reported that the SNPs in IL1B , IL6 , IL4 , IL10 , IL12B , IL1A , IFNG , TNF , PTGS2 (prostaglandin-endoperoxide synthase 2), CTSG (cathepsin G), VDR (vitamin D receptor), MMP1 (matrix metalloproteinase 1), PLAT (plasminogen activator, tissue type), and BAX (Bcl-2 associated X) increased the risk of bacterial OM, whereas those in IL1RN (IL-1 receptor antagonist) and TLR2 (toll-like receptor 2) could protect against OM [ 66 ]. These OM-related genes encode for cytokines, enzymes and proteins involved in inflammatory pathways and in host defense against pathogenic microorganisms, suggesting that inflammation plays a pivotal role in OM development.…”
Section: Sle and Osteomyelitismentioning
confidence: 99%